Construction of defective cobalt oxide for methane combustion by oxygen vacancy engineering. (30th June 2021) - Zhang, Xin; Jin, Xin; Bao, Liurui; Zhang, Mingchao; Song, Ruiming; Yu, Wei; Zhang, Hongbo; Huang, Wei; Su, Weiguang; Li, Xingyun
Abstract : Defects are pivotal to endow metal oxide catalysts with an efficient catalytic oxidation ability. Abstract : Defects are pivotal to endow metal oxide catalysts with an efficient catalytic oxidation ability. Here, a defect engineering strategy was developed by hand-milling Co3 O4 with the aid of Na at room temperature. The facile mechanical–chemical process could kill two birds with one stone: on the one hand, shatter the bulk, and on the other hand create vast oxygen vacancies, which play an important role for surface exposure and intrinsic reactivity enhancement. The as-obtained defective Co3 O4 catalyst delivered a remarkable activity for methane combustion with 50% methane conversion temperature ( T 50 ) of 383 °C and 90% methane conversion temperature ( T 90 ) of 459 °C, which are 47 °C and 35 °C lower than those of the pristine Co3 O4 catalyst, respectively. The catalytic performance improvement could be due to the significantly increased amount of active surface oxygen and boosted oxygen mobility induced by the construction of defects. This study provides effective and convenient tactics to afford advanced catalysts for methane activation and other oxidative reactions.